Dielectric Responses of Polyurethane/Zinc Oxide Blends for Dry-Type Cast Cold-Curing Resin Transformers - Kúdelčík, Jozef; Hardoň, Štefan; Trnka, Pavel; Michal, Ondřej; Hornak, Jaroslav (Polymers, 2021)
The influence of different concentrations (0.5, 1.0, and 2.0 wt.%) of Zinc Oxide (ZnO) filler on the dielectric properties of the cold-curing polyurethane (PU) resin is presented in this study. For this purpose, the direct DC conductivity and the broadband dielectric spectroscopy measurements were used to describe the changes in dielectric responses of PU/ZnO nanocomposites over the frequency and temperature range, respectively. It can be stated that, the 1.0 wt.% nanoparticles and lower caused a decrease in the real relative permittivity compared to the pure PU resin, while the higher concentration of nanoparticles for frequencies above 1 Hz had the opposite effect. The presence of nanoparticles in the polyurethane resin affected the segmental dynamics of the polymer chain and changed a charge distribution in the given system. These changes caused a shift of local relaxation peaks in the spectra of imaginary permittivity and dissipation factor of nanocomposites. It is suggested that the temperature-dependent transition of the electric properties in the nano-composite is closely associated with the α-relaxation and intermediate dipolar effects (IDE).
Keywords: zinc oxide; dielectric relaxation; dry-type transformers; broadband dielectric spectroscopy; polyurethane; cold-curing, nanocomposites